Pentalogy of Cantrell: Prenatal Diagnosis, Delivery, and Immediate Postnatal Surgical Repair - Araujo Júnior, Edward; Carrilho, Milene Carvalho; Toneto, Bruno Rodrigues; Guilhen, José Cicero (Journal of Neonatal Surgery, 2017)
Pentalogy of Cantrell (PC) is a congenital anomaly characterized by a defect in the lower sternum, anterior diaphragm, and anterior abdominal wall; ectopia cordis; and congenital heart disease. It is a very rare congenital anomaly and the prenatal diagnosis is possible in the beginning of second trimester of pregnancy using the conventional ultrasonography. The prognosis is poor with high rates of perinatal mortality. We present a case report of prenatal diagnosis of PC at 22 weeks and 3 days of gestation. We emphasize the prenatal care follow up in a tertiary reference center, the parental counseling, the planning of delivery, and the management of newborn by a multidisciplinary team, including the description of immediate postnatal surgical repair.